Bouldering psychotherapy reduces depressive symptoms even when general physical activity is controlled for: A randomized controlled trial - Stelzer, Eva-Maria; Book, Stephanie; Grässel, Elmar; Hofner, Benjamin; Kornhuber, Johannes; Luttenberger, Katharina (Heliyon, 2018)
Background: Bouldering psychotherapy (BPT) combines psychotherapeutic elements with physical activity (PA). It might be effective for reducing symptoms of depression, but so far, no study has assessed individuals' levels of PA to control for whether positive effects on depression can also be found when adjusting for participants' levels of PA. This is important because PA itself has been proven effective in reducing depression and therefore might be an important variable to account for - especially in therapies using sport as one therapeutic mechanism. Methods: Using a waitlist control group design, outpatients with depression were assessed at baseline and after eight, 16, and 24 weeks. The intervention group took part in an eight-week bouldering psychotherapy which met once a week for three hours. Self-report measures before and after the intervention included the Symptom Checklist-90-R (SCL-90-R), the Beck Depression Inventory (BDI-II), and the questionnaire on resources and self-management skills (FERUS). PA was assessed during the first 16-week period via FitBit Zip accelerometers. Results: Altogether, 47 complete cases (20 men and 27 women) were included in the final analyses. Depression scores dropped by up to 6.74 (CI 2.80-10.67) points on the SCL-90-R depression scale and by up to 8.26 (CI 4.21-12.31) points on the BDI-II during the BPT intervention, the control group remained stable (SCL-90-R Cohen's d = 0.60; BDI-II: Cohen's d = .50). All Participants accrued an average of 6,515 steps per day, which is considered "low-active." Participants of the BPT intervention were significantly more likely to reduce their depressive symptoms (p = .025) than participants of the control group, even when PA was controlled for in a regression analysis. Limitations: Limitations of the study are the relatively small number of patients and the assessment of outcome scores via self-report. Conclusions: This study provides evidence that short-term BPT can be effective for reducing symptoms of depression even if controlled for other therapeutically active confounders including antidepressant medication, psychotherapy and general level of PA.
EVALuna2:211633

German version of the Inventory of Motivations for Hospice Palliative Care Volunteerism: Are there gender differences? - Stelzer, Eva-Maria; Lang, Frieder; Hörl, Melanie; Kamin, Stefan; Claxton-Oldfield, Stephen (American Journal of Hospice & Palliative Medicine, 2018)

Indoor rock climbing (bouldering) as a new treatment for depression: study design of a waitlist-controlled randomized group pilot study and the first results - Luttenberger, Katharina; Stelzer, Eva-Maria; Foerst, Stefan; Schopper, Matthias; Kornhuber, Johannes; Book, Stephanie (BMC Psychiatry, 2015)
Depression is one of the most common diseases in industrialised nations. Physical activity is regarded as an important part of therapeutic intervention. Rock climbing or bouldering (rock climbing to moderate heights without rope) comprises many aspects that are considered useful, but until now, there has been hardly any research on the effects of a bouldering group intervention on people with depression. The purpose of this controlled pilot study was twofold: first, to develop a manual for an eight-week interventional program that integrates psychotherapeutic interventions in a bouldering group setting and second, to assess the effects of a bouldering intervention on people with depression.The intervention took place once a week for three hours across a period of eight weeks. Participants were randomly assigned to the two groups (intervention vs. waitlist). The intervention group began the bouldering therapy immediately after a baseline measurement was taken; the waitlist participants began after an eight-week period of treatment as usual. On four measurement dates at eight-week intervals, participants completed the Beck Depression Inventory II (BDI-II), the symptom checklist-90-R (SCL-90), the questionnaire on resources and self-management skills (FERUS), and the attention test d2-R. A total of 47 participants completed the study, and the data were analysed with descriptive statistics. Cohen's d was calculated as a measure of the effect size. For the primary hypothesis, a regression analysis and the Number Needed to Treat (NNT) (improvement of at least 6 points on the BDI-II) were calculated.After eight weeks of intervention, results indicated positive effects on the measures of depression (primary hypothesis: BDI-II: Cohen's d = 0.77), this was supported by the regression analysis with "group" as the only significant predictor of a change in depression (p = .007). The NNT was four.These findings provide the first evidence that therapeutic bouldering may offer an effective treatment for depression. Further research is required.Current controlled trials, ISRCTN17623318 , registered on July 15(th) 2015.
EVALuna2:23684

Motivations of German Hospice Volunteers: How Do They Compare to Nonhospice Volunteers and US Hospice Volunteers? - Stelzer, Eva-Maria; Lang, Frieder (American Journal of Hospice and Palliative Medicine, 2016)
We examined reasons of volunteering for hospice and nonhospice organizations in a study with 125 volunteers (22-93 years) from the United States and Germany. Motives of US and German hospice volunteers revealed similarities and few differences. Hospice volunteers are involved because they seek to help others, seek new learning experiences, seek social contacts, or seek personal growth. The US hospice volunteers reported motives related to altruistic concerns, enhancement, and social influence as more influential, while German hospice volunteers rated career expectations as being more important. Comparison of German hospice with nonhospice volunteers revealed stronger differences: German hospice volunteers scored higher on altruistic motives, while German nonhospice volunteers yielded higher scores on self-serving motives. Findings contribute to improved understanding of volunteering motivation and of activating or retaining hospice volunteers.
Keywords: hospice; palliative care; volunteering; motivation; recruitment; retention